Immunomodulatory role of microRNAs transferred by extracellular vesicles - Fernández-Messina, Lola (Biol Cell, 2015)
The immune system is composed of different cell types localized throughout the organism to sense and respond to pathological situations while maintaining homeostasis under physiological conditions. Intercellular communication between immune cells is essential to coordinate an effective immune response and involves both cell-contact dependent and independent processes that ensure the transfer of information between bystander and distant cells. There is a rapidly growing body of evidence on the pivotal role of extracellular vesicles (EVs) in cell communication and these structures are emerging as important mediators for immune modulation upon delivery of their molecular cargo. In the last decade, EVs have been shown to be efficient carriers of genetic information, including microRNAs, that can be transferred between cells and regulate gene expression and function on the recipient cell. Here we review the current knowledge of intercellular functional transfer of EV-delivered microRNAs and their putative role in immune regulation.